Investigating the Relationship between the Manning Coefficients (n) of a Perforated Subsurface Stormwater Drainage Pipe and the Hydraulic Parameters - Abdullah J.; Mohd Arif Zainol M.R.R.; Riahi A.; Zakaria N.A.; Yusof M.F.; Shaharuddin S.; Alias M.N.; Mohd Kasim M.Z.; Abdul Aziz M.S.; Mohamed Noor N.; Zawawi M.H.; Ikhsan J. (MDPI, 2024)
Subsurface perforated pipes drain infiltrated stormwater runoff while attenuating the peak flow. The Manning roughness coefficient (n) was identified as a fundamental parameter for estimating roughness in various subsurface channels. Hence, in this work, the performance of a six-row non-staggered sand-slot perforated pipe as a sample of the subsurface drainage is investigated experimentally in a laboratory flume at Universiti Sains Malaysia (USM) aimed at determining the Manning roughness coefficients (n) of the pipe and assessing the relationship between the Mannings n and the hydraulic parameters of the simulated runoff flow under the conditions of the tailgate channel being opened fully (GFO) and partially (GPO), as well as the pipe having longitudinal slopes of 1:750 and 1:1000. Water is pumped into the flume at a maximum discharge rate of 35 L/s, and the velocity and depth of the flow are measured at nine points along the inner parts of the pipe. Based on the calculated Reynolds numbers ranging from 38,252 to 64,801 for both GFO and GPO conditions, it is determined that most of the flow in the perforated pipe is turbulent, and the calculated flow discharges and velocities from the outlets under GFO are higher than the flow and velocity rates under GPO with similar pipe slopes of 1:750 and 1:1000. The Manning coefficients are calculated at nine points along the pipe and range from 0.004 to 0.009. Based on the ranges of the calculated Mannings n, an inverse linear relationships between the Manning coefficients and the flow velocity under GFO and GPO conditions are observed with the R2 of 0.975 and 0.966, as well as 0.819 and 0.992 resulting from predicting the values of flow velocities with the equations v = ((0.01440 ? n)/0.009175), v = ((0.01330 ? n)/0.00890), v = ((0.02007 ? n)/0.01814), and v = ((0.01702 ? n)/0.01456) with pipe slopes of 1:750 and 1:1000, respectively. It is concluded that since the roughness coefficient (Mannings n) of the pipe increases, it is able to reduce the flow velocity in the pipe, resulting in a lower peak of flow and the ability to control the quantity of storm water in the subsurface urban drainages. 2023 by the authors.